The effect of collaborative writing strategy with google docs and motivation towards eighth grade students’ writing ability on descriptive text - Reka Agustin; Rusman Roni (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study was to investigate the effect of collaborative writing strategy with google docs and motivation towards eight grade students’ writing abilty on descriptive text at SMPN 12 Palembang. The population of this study was all the eight grade students of SMPN 12 Palembang which total is 252 students. The sample was 64 students taken by using statified random sampling. In carrying out of the research, the writer used an experimental method : factorial design. The writer distributed pretest, posttest, and motivation questionnairein collecting data. Then in analyzing the data the writer used paired sample test, independent sample t-test and two way ANOVA. The result of this study analysis indicated that, first, there was a significant difference between writing ability of the eighth grade students with high motivation and those with low motivation taught through collaborative writing strategy with google docs. Second, there was a significant difference between writing ability of the eighth grade students with high motivation and low motivation taught through conventional method. Third, there was a significant difference between writing ability of the eighth grade students with high motivation and low motivation taught through collaborative writing strategy with google docs and those with high motivation and low motivation taught through conventional method. Fourth, there were significant interaction effect of collabotrative writing strategy with google docs and the eighth grade students’ motivation towards writing ability.